Respostas

2013-05-12T20:29:13-03:00

 Observe que :

 

 

   y - 3. ( y - 2 ) - 10                  -------------               2y - 2. ( y - 3 )

 

   y - 3y + 6 -10                         -------------               2y - 2y + 6

 

     - 2y - 4                                  -----------                   0 + 6

 

    - ( 2y + 4 )                             -----------                       +6

 

 

fazendo y = 0

        temos:   -( 2 x 0 + 4 ) =  - 4

 

fazendo y = 1

 

          temos:  - ( 2 x 1 + 4 ) = - 6

 

 

 

 

fazendo y = -1 

           vem:      - ( 2 x (-1) +4 ) = -( -2 + 4 ) = - ( + 2 ) = - 2

 

           se  y = - 2  ---->    -  ( -4+4)= 0

 

            se y = -3  ----->    - ( -6+4 ) = +2

 

            se y = -4   ------>    - (-8 +4) = +4

 

            se y = - 5  ------>    - ( -10+4) = +6

 

            se y = -6 ---->     - (-12+4) = +8

 

 

A 2º equação é maior que a 1ª  quando assume  os valores do no intervalo : aberto em -6 até +∞..